Exploring the Impacts of Shrub‐Overwash Feedbacks in Coastal Barrier Systems With an Ecological‐Morphological Model. Issue 3 (4th March 2022) - Reeves, Ian R. B.; Goldstein, Evan B.; Moore, Laura J.; Zinnert, Julie C.
Abstract: Shrubs are common – and presently expanding – across coastal barrier interiors (the land between the foredune system and back‐barrier bay), and have the potential to influence barrier morphodynamics by obstructing cross‐shore overwash flow. The ecological and geomorphological consequences of ecomorphodynamic couplings of the barrier interior, however, remain largely unexplored. In this contribution, we add an ecological module of shrub expansion and mortality to a spatially‐explicit exploratory model of barrier evolution (Barrier3D) to explore the effects of shrub‐barrier feedbacks. In our model simulations, we find that the presence of shrubs significantly alters barrier morphology and behavior. Over timescales of decades to centuries, barriers with shrubs (relative to those without) tend to be narrower, migrate landward more slowly, and have a greater proportion of subaerial volume distributed toward the ocean‐side of the barrier. Shrubs also tend to increase the likelihood of discontinuous barrier retreat, a behavior in which a barrier oscillates between periods of transgression and relative immobility, because shrubs induce prolonged periods of barrier immobility by obstructing overwash flow. However, shrubs can increase barrier vulnerability to drowning by preventing periods of transgression needed to maintain barrier elevation relative to rising sea levels. Additionally, physical barrier processes influence shrub expansion in our simulations; we find that greater dune erosion and overwash disturbance tends to slow the rate of shrub expansion across the barrier interior. Complementing recent observational studies of barrier islands in Virginia, USA, our results suggest that interior ecology can be a key component of barrier evolution on annual to centurial timescales. Plain Language Summary: Shrubs are common on coastal barriers, typically found sheltered behind dunes. During large storms, sand from the beach is washed into the barrier interior and beyond in a process called overwash. Overwash tends to cause the barrier to gain elevation relative to sea level, and also move the whole barrier landward. Shrubs, however, can obstruct this flow across a barrier. Here we explore how shrubs blocking overwash can impact barrier change, and how barrier change affects the growth of shrubs. We do this by adding new code to represent shrubs to an existing computer model of barrier evolution. Results from the computer model suggest that barriers with shrubs are typically narrower and tend to move landward more slowly compared to barriers without shrubs. Additionally, barriers with shrubs are more likely to move landward in a stop‐and‐go manner, switching between periods of fast landward motion and no motion. Therefore, barriers with shrubs are less likely to smoothly and continuously move landward. We also find that shrubs expand more slowly across barriers when storms cause significant dune erosion and overwash disturbance. Our work suggests that including shrubs in barrier models helps us better understand the ecological and geomorphological change of barrier systems. Key Points: Modeled barriers with shrubs tend to be narrower, migrate landward more slowly, and be more strongly skewed volumetrically toward the ocean Shrubs increase the likelihood of discontinuous barrier retreat and, under some conditions, increase barrier vulnerability to drowning Shrubs expand more slowly across barriers experiencing greater dune erosion and overwash disturbance (and vice versa)